Association between serum concentrations of perfluoroalkyl substances (PFAS) and expression of serum microRNAs in a cohort highly exposed to PFAS from drinking water - Xu, Yiyi; Jurkovic-Mlakar, Simona; Li, Ying; Wahlberg, Karin; Scott, Kristin; Pineda, Daniela; Lindh, Christian H.; Jakobsson, Kristina; Engström, Karin (Environment international, 2020)
•MiRNA expression in a cohort highly exposed to perfluoroalkyl substances (PFAS)•MiR-101-3p, miR-144-3p and miR-19a-3p were downregulated with increased serum PFAS.•In silico analyses showed 7 target genes for these 3 miRNAs to be annotated to PFAS.•Ingenuity pathway analyses suggest these miRNAs associated to several health effects.•This study propose epigenetic mechanisms as a mode of action of PFAS toxicity. Perfluoroalkyl substances (PFAS) are widespread synthetic substances with various adverse health effects. Not much is known about the modes of action of PFAS toxicity, but one likely mechanism is alteration of microRNA expression. To investigate whether PFAS exposure is associated with altered microRNA expression in serum. We selected women from the Ronneby cohort, with high exposure to perfluorooctane sulfonic acid (PFOS) and perfluorohexane sulfonic acid (PFHxS), emanating from drinking water contaminated by firefighting foam, and a control group of women from a neighbouring municipality without drinking water contamination. Serum levels of PFAS were analysed using LC/MS/MS. High coverage microRNA expression was analysed by next generation sequencing (NGS) in 53 individuals to screen for microRNAs associated with PFAS exposure. After verification by qPCR, associations between PFAS exposure and expression of 18 selected microRNAs were validated by qPCR in 232 individuals. In silico functional analyses were performed using Ingenuity pathway analysis (IPA). Three microRNAs were consistently associated with PFAS exposure in the different steps of the study: miR-101-3p, miR-144-3p and miR-19a-3p (all downregulated with increasing exposure). In silico functional analyses suggested that these PFAS-associated microRNAs were annotated to e.g. cardiovascular function and disease, Alzheimer’s disease, growth of cancer cell lines and cancer. Seven predicted target genes for the downregulated microRNAs were annotated to PFAS in IPA knowledge database: DNA methyltransferase 3 alpha (DNMT3a), epidermal growth factor receptor (EGFR), 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), nuclear receptor subfamily 1, group H, member 3 (NR1H3), peroxisome proliferator-activated receptor alpha (PPARα), prostaglandin-endoperoxide synthase 2 (PTGS2), and tumour growth factor alpha (TGFα). PFAS exposure was associated with downregulation of specific microRNAs. Further, in silico functional analyses suggest potential links between the specific PFAS-associated microRNAs, specific microRNA target genes and possibly also health effects.